31 Days Before Your CCENT Certification Exam : a Day-By-Day Review Guide for the ICND1 (100-101) Certification Exam, Second Edition - Johnson, Allan (Cisco Press, 2013)
31 Days Before Your CCENT Certification Exam Second Edition A Day-By-Day Review Guide for the ICND1 (100-101) Certification Exam 31 Days Before Your CCENT Certification Exam offers you a personable and practical way to understand the certification process, commit to taking the 100-101 ICND1 certification exam, and finish your preparation using a variety of Primary and Supplemental study resources. With a CCENT (Cisco Certified Entry Networking Technician) certification, a network professional demonstrates the skills required for entry-level network support positions-the starting point for many successful careers in networking. CCENT is the first step toward achieving CCNA certification. Sign up for the ICND1 exam and use the book's day-by-day guide and checklist to organize, prepare, and review. Each day in this guide breaks down an exam topic into a manageable bit of information to review using short summaries. A Study Resources section provides you with a quick reference for locating more in-depth treatment of a day's topics within the Primary and Supplemental resources. The features of the book empower you to fit exam preparation into a busy schedule: --Visual calendar summarizing each day's study topic --Checklist providing advice for preparation activities leading up to the exam --Description of the 100-101 ICND1 exam organization and sign-up process --Strategies from the author to be mentally, organizationally, and physically prepared for exam day --Conversational tone, which makes your study time more enjoyable Primary Resources: Cisco CCENT/CCNA ICND1 100-101 Official Cert Guide ISBN: 9781587143854 Interconnecting Cisco Network Devices, Part 1 Foundation Learning Guide ISBN: 9781587143762 Introduction to Networks Companion Guide ISBN: 9781587133169 Introduction to Networks Lab Manual ISBN: 9781587133121 Routing and Switching Essentials Companion Guide ISBN: 9781587133183 Routing and Switching Essentials Lab Manual ISBN: 9781587133206 Supplemental Resources: CCENT Practice and Study Guide ISBN: 9781587133459 Cisco CCENT ICND1 100-101 Flash Cards and Exam Practice Pack ISBN: 9781587203992 CCNA Routing and Switching Portable Command Guide, 3e ISBN: 9781587204302 Cisco CCENT ICND1 100-101 Network Simulator ISBN: 9780789750433.